2018
DOI: 10.1542/peds.2017-3406
|View full text |Cite
|
Sign up to set email alerts
|

Imaging in Pediatric Concussion: A Systematic Review

Abstract: These data highlight essential priorities for future research (eg, common data elements) that are foundational to progress the understanding of pediatric concussion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 80 publications
1
43
0
Order By: Relevance
“…Unfortunately, few studies have utilized dMRI in pediatric-only populations with concussion. A recent systematic review on pediatric neuroimaging (Schmidt et al, 2018) found that only one dMRI study thus far has evaluated microstructural changes in the corpus callosum long after pediatric concussion (Van Beek, Vanderauwera, Ghesquière, Lagae, & De Smedt, 2015). This longitudinal study found white matter alterations acutely after injury and these alterations had resolved by 6 months post-injury (Van Beek et al, 2015).…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations
“…Unfortunately, few studies have utilized dMRI in pediatric-only populations with concussion. A recent systematic review on pediatric neuroimaging (Schmidt et al, 2018) found that only one dMRI study thus far has evaluated microstructural changes in the corpus callosum long after pediatric concussion (Van Beek, Vanderauwera, Ghesquière, Lagae, & De Smedt, 2015). This longitudinal study found white matter alterations acutely after injury and these alterations had resolved by 6 months post-injury (Van Beek et al, 2015).…”
Section: Introductionmentioning
confidence: 90%
“…Advanced neuroimaging techniques such as diffusion magnetic resonance imaging (dMRI) have provided a noninvasive means of examining and quantifying white matter microstructure through in vivo measures of water diffusion (Beaulieu, 2002;Bigler, 2013). Studies utilizing dMRI in concussion populations have demonstrated that the corpus callosum is a commonly altered white matter pathway acutely following concussion (Aoki, Inokuchi, Gunshin, Yahagi, & Suwa, 2012;Dodd, Epstein, Ling, & Mayer, 2014;Schmidt et al, 2018;Virji-Babul et al, 2013), likely due to its position on the midline axis that increases its risk of axonal shearing (Aoki et al, 2012). Axonal shearing can lead to alterations in diffusion metrics such as fractional anisotropy (FA), mean diffusivity (MD), axial diffusivity (AD), and radial diffusivity (RD), with more severe injuries tending to cause more drastic alterations in diffusivity (Kraus et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[36][37][38] Magnetic resonance imaging studies using modern techniques such as diffusion tensor imaging suggest that microstructural pathology (eg, weakened integrity of long white matter tracts) can also be a feature of mTBI, 39 although the nature, location, time course, and clinical significance of such changes are unclear. [40][41][42] Clinical presentation and diagnosis mTBI can be challenging to diagnose in any setting because the acute signs and symptoms of altered mental status (AMS) are often subtle and transient, and available diagnostic tests (eg, CT) are not sensitive. These issues may be compounded in primary care, where patients are often first evaluated days or even weeks after an injury event and factors that mimic mTBI-like symptoms (fig 1) may have emerged.…”
Section: Pathophysiologymentioning
confidence: 99%